Membrane penetration of nitrogen and its effects on nitrogen removal in dual-chambered microbial fuel cells. (June 2022) - Jin, Xiaojun; Yang, Nuan; Liu, Hong; Wang, Sha
Abstract: Owing to membrane penetration, a novel route of nitrogen removal was proposed in a dual-chamber microbial fuel cell with a proton exchange membrane (PEM). The results showed that NH4 + -N rapidly migrated across PEM with a mass transfer coefficient ( K A ) of 1.79 ± 0.51 × 10 −4  cm s −1, 50% of which was oxidized to NO3 − -N in the cathode chamber, then the remainder being eliminated by short-cut nitrification/denitrification. Meanwhile, NO3 − -N went across the PEM again with a low K A of 5.50 ± 0.24 × 10 −6  cm s −1, and was subsequently reduced via anodic denitrification. In the anode, the functional microorganisms were divided into exoelectrogenic bacteria (46.2%) and denitrifying bacteria (37.3%), while the dominated bacteria were mainly affiliated with nitrifying bacteria (19.6%) and aerobic denitrifying bacteria (52.9%) in the cathode. These findings provide a new insight into nitrogen removal during bioelectrochemical treatment of actual wastewater. Graphical abstract: Image 1 Highlights: All forms of nitrogen can migrate across PEM in dual-chamber MFCs. NH4 + is removed by complete nitrification and short nitrification/denitrification. Simultaneous nitrification and denitrification occur aerobically in the cathode. Anodic denitrification is the main route of nitrate reduction.